Weight and height centiles of Argentinian children and adolescents: a comparison with WHO and national growth references - Orden, Alicia B.; Apezteguía, María C. (Annals of human biology, 2016)
Background: Studies in several countries comparing the performance of WHO references and their own national growth standards reported differences that could affect screening and growth monitoring. Aim: To estimate weight and height centiles on a sample of Argentinian children and adolescents and compare selected centiles with WHO and national growth references. Subjects and methods: A cross-sectional school survey was conducted on 6239 boys and girls aged 5-18. Data were collected between 2005-2009 in Santa Rosa, Argentina. Smoothed weight and height centiles were estimated by the LMS method and compared with WHO 2007 and Argentinian (ARG) growth references. Results: Weight centiles were higher than those of WHO and ARG. Height centiles were above the ARG and below the WHO ones. The greatest differences with ARG were seen before puberty and then declined up to age 18. In contrast, differences with WHO increased from puberty onwards. Conclusion: Compared with the ARG reference, linear growth of these schoolchildren shows a secular acceleration without substantial improvements in the adult height. In relation to WHO, the results suggest that around the adolescent growth spurt differences in linear growth between populations became larger, limiting the clinical usefulness of international growth references in adolescents.